Beyond the Physical Classroom: A Comparative Performance Analysis of Online and Traditional Accounting Pedagogy - Thami Isaac Makhoba (Managere: Indonesian Journal of Educational Management, 2026)
This study aims to analyze the comparative effectiveness of online and traditional accounting pedagogy in a resource-constrained higher education context in South Africa. The rapid digital transformation of higher education has shifted learning from physical classrooms to virtual environments, raising concerns about student engagement and learning quality. In accounting education, this transition is critical because it helps develop technically competent professionals. This study employs an interpretivist paradigm with a qualitative case study approach. Data were collected through narrative and semi-structured interviews with 16 final-year accounting students and analyzed using thematic analysis. The findings reveal that online learning enhances autonomy through self-paced study and access to digital resources, creating a “personalized tutor” effect. However, a significant digital divide persists, with rural and township students facing infrastructural barriers such as poor internet connectivity and unreliable electricity. Additionally, the “hybridity paradox” shows students value flexibility but still depend on social interaction, often forming peer-led learning networks. Student adaptability varies based on demographic factors such as age, digital literacy, and responsibilities. The implications of this study highlight the need for higher education institutions to strengthen digital infrastructure, particularly through affordable connectivity solutions, while maintaining structured hybrid learning models that preserve essential social interaction in accounting education.